Transcriptomics and Metabolomics Changes Triggered by Inflorescence Removal in Panax notoginseng (Burk.) - Bai, Yu; Liu, Haijiao; Pan, Jianying; Zhang, Shiyan; Guo, Yixin; Xian, Yisha; Sun, Zhirong; Zhang, Zilong (Frontiers in Plant Science, 2021)
The root of Panax notoginseng (Burk.), in which saponins are the major active components, is a famous traditional Chinese medicine used to stop bleeding and to decrease inflammation and heart disease. Inflorescence removal increases the yield and quality of P. notoginseng, but the underlying molecular mechanisms are unknown. Here, the differences between inflorescence-removal treatment and control groups of P. notoginseng were compared using transcriptomics and metabolomics analyses. Illumina sequencing of cDNA libraries prepared from the rhizomes, leaves and roots of the two groups independently identified 6,464, 4,584 and 7,220 differentially expressed genes, respectively. In total, 345 differentially expressed transcription factors, including MYB and WRKY family members, were induced by the inflorescence-removal treatment. Additionally, 215 differentially expressed genes involved in saponin terpenoid backbone biosynthetic pathways were identified. Most genes involved in the mevalonic acid and methylerythritol phosphate pathways were activated by inflorescence removal. The co-expression analysis showed that the low expression levels of flavonoid biosynthesis-related genes (e.g., C4H and F3H) decreased the biosynthesis and accumulation of some flavonoids after inflorescence removal. The results not only provide new insights into the fundamental mechanisms underlying the poorly studied inflorescence-removal process in P. notoginseng and other rhizome crops, but they also represent an important resource for future research on gene functions during inflorescence-removal treatments and the reproductive stage.